GLOBAL MARITIME AXIS UNDER JOKOWI: THE OPPORTUNITIES AND CHALLENGES FOR INDONESIA’S NATIONAL SECURITY INTEREST - Muhamad Linggar Pangestu (HI 16 UMY 108, 2016)
*108 This paper will analyze the reasons why Jokowi has decided Global Maritime Axis to achieve Indonesia National Security Interest. Jokowi mentions about the five visions of Global Maritime Axis, which are maritime culture, seafood based industry, the infrastructure related to maritime connectivity, maritime diplomacy, and maritime defense force. According to Alfred Mahan’s six elements of Sea Power, Indonesia is already in accordance with all the six elements such as its geographic conditions, physical conditions, the number of people, etc. Those all could create opportunities for Indonesia to achieve the maritime power. But there are also some several challenges for Jokowi visions on Global Maritime Axis, such as overlapping and discoordination on several departments such as Bakamla (the Maritime Security Board) and others Maritime’s departments. Keywords: Global Maritime Axis; Sea Power; Navy; National Security Interest; Indonesian Sea; Geopolitics